Strengthening the Function of Notarial Deeds in Guaranteeing the Validity of Government Electronic Contracts - Kadek Septianingsih; I Wayan Parsa; I Wayan Novy Purwanto; Ida Bagus Erwin Ranawijaya (Journal of Sustainable Development Science, 2026)
This study aims to analyze the strengthening of the function of notarial deeds in guaranteeing the validity of electronic contracts in government procurement of goods and services. The development of e-procurement systems has driven a significant digital transformation in the procurement process, thus demanding stronger legal certainty, particularly in the aspects of the validity and evidentiary power of electronic contracts. The research method used is a normative juridical approach by examining relevant laws and legal concepts. The results show that although electronic contracts have been legally recognized, their status remains as private deeds with limited evidentiary power. Notarial deeds, as authentic deeds, have perfect evidentiary power and can strengthen legal certainty in electronic contracts. However, the absence of explicit regulations regarding the involvement of notaries in electronic contracts creates a normative vacuum. Therefore, the concept of cyber notary is an adaptive solution in integrating the role of notaries into digital systems. Strengthening regulations, harmonization of regulations, and support for technological infrastructure are needed to optimize the role of notaries in guaranteeing the validity of electronic contracts. This research is expected to contribute to the development of laws that are responsive to developments in information technology.